Inverse PHI slotted antenna design for RFID application - Md Nor, Norazura (2014)
In RFID application, the antennas are the most paramount components required to engender a communication link between tag and reader. Dual band or multiple band antennas is designed to prevent excessive radiation effects due to the use of various sets of reader antenna in a system. Dual-band antenna is designed to operate at a frequency of 900MHz and 2.45GHz to meet the needs of RFID applications. Accordingly, these antennas help reduce the amount of RFID reader antennas in the RFID system. Planar monopole antennas are the most suited for indoor and mobile applications because of their low profile, light weight and omnidirectional characteristics. With the omnidirectional radiation pattern characteristic, this antenna will suit for portable RFID reader application. The major consideration for antenna design for handheld/ portable reader RFID reader applications is the compact size, while the antenna gain and bandwidth are not critical issues. Planar monopole can be designed in a variety of shapes in order to obtain enhanced bandwidth, dual band and ultra-wideband operation. Inverse Phi Slotted Antenna has been introducing based on planar antenna concept and able to provide a dual-band bandwidth for RFID application. This thesis provides a detailed study of the design of Inverse Phi Slotted Antenna to facilitate linear polarized and dual band operation. The design parameters of the antenna have been calculated utilizing the transmission line model. The effect of antenna dimensions on the performance of antennas has been discussed. This antenna is designed to use the technique of reactive load for the operation of dual- band RFID reader. The center frequencies of these bands are controlled by the electrical length of slots. A moderate gain has successfully achieved.